A New Challenge on Consumer Protection with Disclaimer Inclusion in E-Commerce Sites in Indonesia - Shahrullah, Rina Shahriyani; Syarief, Elza; Hariyanto, Jerry (Jurist-Diction, 2024)
AbstractThe development of information and technology has brought the economy to a new stage known as e-commerce. The presence of e-commerce also presents a new problem in society, namely the presence of a disclaimer. To examine these problems, this research uses normative legal research methods. This research shows that the disclaimer is a form of standard clause. As a form of e-commerce consumer protection, the standard clause must comply with the provisions regarding standard clauses as stipulated in statutory regulations. In Indonesia, e-commerce is regulated in Law No. 19 of 2016 concerning Electronic Information and Transactions. So, the implementation of the disclaimer in e-commerce transactions must be adjusted to the existing laws in Indonesia. Keywords: E-Commerce; Disclaimer; Consumer Legal Protection.